Problems and prospects for the development of the first market of lease land in Ukraine - Hunko, L.; Kolhanova, I. (Land Management, Cadastre and Land Monitoring, 2017)
The land is the main asset of the farmer. The basic production of agricultural products, the food security of the state and its export potential today depend directly on the ability of agricultural producers to conduct sustainable production. However, in addition to the natural elements that stand in the way of stabilizing the situation in the field of agriculture, we also have a chronic presence of numerous "man-made" problems that remain unsettled for years. One of the most significant and painful of them is the state registration of the right to lease land. Long-term disorder, corporate wars between state authorities for the right to land relations, negligent attitude to information on land rights and their encumbrances, the shifting of competence among registrars of land tenure rights continue to cause complaints from agricultural producers. But the peculiarities of the legal regulation of the state registration of the right to lease land for agricultural purposes did not become the subject of a separate scientific study. Consequently, the purpose of this work is to study and analyze the problems of legal regulation of state registration of the right to lease land and to find an acceptable option for their further solution.Since the reform of the agrarian sector of Ukraine, the most common form of land use in agricultural production is the use of land by agricultural producers on a lease. The advantage of leasing relations in agricultural production is enshrined in the Concept of the State Target Program for Land Relations Development in Ukraine for the period up to 2020, which was approved by the Resolution of the Cabinet of Ministers of Ukraine dated June 17, 2009 No. 743-p.The right to lease a land plot is mediated by a contract concluded in accordance with the Article 20 of the Law of Ukraine "On land lease" is subject to mandatory state registration,on the other hand in Article 125 of the Land Code of Ukraine, it is stated that the right to lease a land plot arises from the moment of state registration of this right. Thus, the fact of registration of the lease contract for agricultural land is a necessary condition for determining the legality of land use of agricultural producers.The state registration of the right to lease a land plot of agricultural land is preceded by a state registration of a land plot that is the subject of a lease and a state registration of the ownership of such a land plot. The right to lease a land plot used for agricultural production arises from the moment of state registration of this right. The intended purpose and type of use within the purpose of the leased land should be identical both in the lease agreement of the land plot and in the State Land Cadastre. State registration of land lease agreements for agricultural purposes provides legal guarantees regarding the actual use of land in agricultural production activities.Key words: land lease, state registration of lease rights, lease of land, real rights, state land cadastre.